2010
DOI: 10.1212/wnl.0b013e3181eccfb5
|View full text |Cite
|
Sign up to set email alerts
|

Zonisamide discontinuation due to psychiatric and cognitive adverse events

Abstract: We have identified clinically relevant risk factors associated with the discontinuation of ZNS. Our findings support the concept that selected patients are relatively more vulnerable to CNS adverse events when exposed to ZNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 23 publications
1
37
0
1
Order By: Relevance
“…Although CAEs are often the most common reason for discontinuation of zonisamide, perhaps only 5.8% will withdraw from treatment for this reason [White et al 2010]. There are conflicting findings as to the prevalence of CAEs.…”
Section: Zonisamidementioning
confidence: 99%
“…Although CAEs are often the most common reason for discontinuation of zonisamide, perhaps only 5.8% will withdraw from treatment for this reason [White et al 2010]. There are conflicting findings as to the prevalence of CAEs.…”
Section: Zonisamidementioning
confidence: 99%
“…Patients with a history of psychiatric condition were twice as likely to have IACEs to two or more AEDs compared to patients without a history of psychiatric condition. A past psychiatric history has been shown to be an independent predictor of ACEs in previous studies [16,17]. As postulated in a prior study by Kanner et al, concomitant anxiety and depression might increase the "complaint rate" (i.e., the tendency to report side effects) [16].…”
Section: Discussionmentioning
confidence: 81%
“…Additionally, there was no specific crosssensitivity between TPM and ZNS in our study. Two prior studies also reported relatively low rates of adverse cognitive and psychiatric effects of ZNS [17,27]. The better tolerability profile of ZNS than TPM suggests that properties other than their shared chemical structure are likely causative of cognitive effects.…”
Section: Discussionmentioning
confidence: 90%
“…39 Impaired cognitive function is the most common reason of discontinuation. 40 Dose related decline in attention, memory and verbal fluency has been noted. 41 Usual adult daily dose of zonisamide is 200-600 mg and target range of plasma concentration is 10-40 µg/ml.…”
Section: Zonisamidementioning
confidence: 99%